Connecting foreign language enjoyment and English proficiency levels: The mediating role of L2 motivation - Wang, Haihua; Xu, Lin; Li, Jiaxin (Frontiers in Psychology, 2023)
To further understand the connections between positive emotions, in particular foreign language enjoyment (FLE), L2 motivation, and English achievement, the present study investigated how FLE and L2 motivation contribute to learners’ English achievement and the mediating role of motivation in the pathway. Questionnaires were employed to collect quantitative data from 512 university students learning English as a foreign language (EFL) in China. The results showed that the higher the language proficiency level, the higher the FLE level and the stronger the L2 motivation. Participants reported a significant difference in the private factor of FLE, the ideal L2 self, and the L2 learning experience among different language proficiency groups. Overall, FLE has a positive predictive effect on L2 motivation; however, the influence of different dimensions varies among language proficiency groups. FLE is a positive predictor of English achievement, and motivation partially mediates this pathway. These findings provided an in-depth profile of FLE and L2 motivation of Chinese EFL learners at different language proficiency levels, highlighting the connections between positive emotion, motivation, and English achievement, and the contribution of FLE and L2 motivation in EFL learning. Based on these findings, pedagogical implications are suggested for EFL teaching and learning in Chinese tertiary education.